EFFICACY OF FUNGICIDES AGAINST COLLETOTRICHUM GLOEOSPORIOIDES CAUSING STEM END ROT AND FRUIT DROP IN MANDARIN (Journal of Plant Disease Sciences, 2025)
Mandarin (Citrus reticulata Blanco) is one of India's most important citrus crops, contributing to about 40% of the total citrus cultivation. However, its productivity is severely impacted by stem end rot and preharvest fruit drop, primarily caused by Colletotrichum gloeosporioides. This fungal pathogen spreads rapidly under humid and warm conditions, leading to significant yield losses. The present study was conducted to evaluate the efficacy of various fungicides against C. gloeosporioides using the poisoned food technique in a laboratory setting.Fungal isolates were obtained from diseased mandarin fruits collected from university orchards. Pathogenicity was confirmed using Koch’s postulates. A total of sixteen chemical fungicides were tested for their ability to inhibit mycelial growth. The most effective fungicides at both half dose and recommended dose were:
Keywords: Colletotrichum gloeosporioides; Fungicides; Efficacy; Inhibition; Mandarin